Does an information film about prenatal testing in early pregnancy affect women's anxiety and worries?. (March 2013) - Björklund, Ulla; Marsk, Anna; Öhman, Susanne Georgsson
Abstract: Objective: To explore if an information film about prenatal examinations affects pregnant women's worry and anxiety. Methods: Randomized controlled study. The intervention was an information film about prenatal examinations. Data was collected in gestational week 26 by a questionnaire including the STAI (State-Trait Anxiety Inventory) instrument and further questions about worry. A total of 184 women in the intervention group and 206 in the control group filled in the questionnaire. Results: There were no statistically significant differences between the groups neither in state nor trait anxiety. Regarding worry about the possibility of something being wrong with the baby and worry about giving birth, there were no statistically significant differences between the groups. The women stated that to see the film increased their worry rather than decreased it. Conclusion: An informational film as additional information to complement written and verbal information about prenatal testing does not appear to increase women's anxiety and worries. However, the informational film may cause worry at the time of viewing which should be taken into consideration.